Isolated pulmonary recurrence after resection of pancreatic cancer: the effect of patient factors and treatment modalities on survival. Issue 8 (August 2019) - Groot, Vincent P.; Blair, Alex B.; Gemenetzis, Georgios; Ding, Ding; Burkhart, Richard A.; van Oosten, A. Floortje; Molenaar, I. Quintus; Cameron, John L.; Weiss, Matthew J.; Yang, Stephen C.; Wolfgang, Christopher L.; He, Jin
Abstract: Background: The literature suggests favorable survival for patients with isolated pulmonary recurrence after resection of pancreatic ductal adenocarcinoma (PDAC) as compared to other recurrence patterns. Within this cohort, it remains unclear what factors are associated with improved survival. Methods: Patients who developed pulmonary recurrence after pancreatectomy were selected from a prospective database. Predictors for post-recurrence survival (PRS) were analyzed using a multivariable Cox regression model. Results: Ninety-six patients were included. Median recurrence-free survival (RFS), PRS and overall survival (OS) were 16.3, 18.8 and 39.6 months, respectively. Further systemic treatment and/or metastasectomy ( n  = 64, 67%) was associated with significantly improved PRS and OS when compared to best supportive care ( n  = 35, 22%) (26.3 vs. 5.3 and 48.1 vs. 18.4, respectively; both P  < 0.001). Patients who were able to undergo metastasectomy ( n  = 19) achieved a PRS and OS of 35.0 and 68.9 months, respectively. More than 5 pulmonary lesions, symptoms and CA 19-9 ≥100 U/mL at time of recurrence were predictive of decreased PRS. A recurrence-free interval of >16 months and treatment for recurrence were independently associated with improved PRS. Conclusions: Isolated pulmonary recurrence occurs in 13% of patients with recurrent PDAC and is associated with a median OS of 40 months. Aggressive treatment in highly selected patients was correlated with improved survival.